Pelatihan Penulisan Ilmiah untuk Pokdarwis DWH Bilebante: Memanfaatkan AI dalam Membangun Arsip Pengetahuan Wisata - Latifah, Annisa; Inne Juni Simamora, Vera; Calista Poluan, Regina (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
Bilebante Tourism Village is one of the destinations currently preparing to participate in the Best Tourism Village UNWTO 2026. In this process, the need for systematic and credible documentation has become increasingly important. This community service activity was carried out to address this need, with the primary goal of enhancing the scientific literacy of Pokdarwis DWH Bilebante members through technology-based writing training aimed at producing high-quality tourism knowledge archives. The training was attended by six participants who play a key role in preparing documents for the competition and was conducted in person. The activity methods included a self assessment pre-test, interactive material delivery, discussion sessions, article writing practice, and a self assessment post-test. The materials covered an introduction to scientific articles, paragraph structure, article writing techniques, and the use of ChatGPT for drafting and editing texts. The results of the pre-test, post-test, and article writing practice showed an increase in participants' understanding of scientific writing. The post-test score for the question regarding the ability to write AI-assisted articles increased by 66.6 percent compared to the pre-test. In addition, participants were able to produce complete articles on the theme